2008
DOI: 10.1021/cm703693r
|View full text |Cite
|
Sign up to set email alerts
|

Polyfluoroalkyl, Polyethylene Glycol, 1,4-Bismethylenebenzene, or 1,4-Bismethylene-2,3,5,6-Tetrafluorobenzene Bridged Functionalized Dicationic Ionic Liquids: Synthesis and Properties as High Temperature Lubricants

Abstract: A new class of geminal dicationic ionic liquids was formed with a bridging moiety, such as a polyalkyl ether, polyfluoroalkyl, 1,4-bismethylenebenzene, or 1,4-bismethylene-2,3,5,6-tetrafluorobenzene link, between alkyl-substituted imidazolium rings. Their properties were modified by varying the linker chains and/or alkyl substituents on the imidazolium ring. The polyfluoroalkyl bridged dicationic ionic liquids exhibit the highest densities and viscosities. Although melting points are directly proportional to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(133 citation statements)
references
References 47 publications
3
130
0
Order By: Relevance
“…Thereto, it has been proposed to synthesize IL-lubricants with high thermal stability up to 400 8C, [49,[67][68][69] based on the fact that geminal dicationic ILs possess extremely high thermal stability. [72] 3.…”
Section: Tailored Lubricantsmentioning
confidence: 99%
“…Thereto, it has been proposed to synthesize IL-lubricants with high thermal stability up to 400 8C, [49,[67][68][69] based on the fact that geminal dicationic ILs possess extremely high thermal stability. [72] 3.…”
Section: Tailored Lubricantsmentioning
confidence: 99%
“…1,2 Room temperature ionic liquids with dipositive cations are rare, hence their physical behaviour is not well understood. [3][4][5][6][7][8][9] Tripositive cations are even scarcer. [10][11][12] The interest in dicationic ionic liquids is largely due to their high thermal stability, higher than that normally characterising the corresponding monocationic ionic liquids.…”
Section: Introductionmentioning
confidence: 99%
“…The structures of the dicationic IL (IL2-di) and its monocationic analogue (IL2), which was used as a benchmark in this study, are shown in Figure 1. connecting chain [28][29][30][31] that was associated with better tribological properties, higher stability, lower toxicity and corrosiveness of the dicationic ILs [14,[31][32][33][34][35][36][37][38][39][40][41]. In the literature, there is a consensus of opinions that the good friction-reduction and wearresistant properties of ILs are owed to their ability to form stable adsorbed layers and protective tribofilms [4,27,[42][43][44].…”
Section: Methodsmentioning
confidence: 99%
“…Another approach relies on bridging two cationic head groups by PEG chain. Molecular dynamics simulation and advanced spectroscopy have revealed significant differences in structural heterogeneity and nano-organization between monocationic and geminal dicationic ILs with a long connecting chain [28][29][30][31] that was associated with better tribological properties, higher stability, lower toxicity and corrosiveness of the dicationic ILs [14,[31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%